Термодинамическая модель процесса расходования ресурса электронной аппаратуры - Андрусевич, А. А. (Eastern-European Journal of Enterprise Technologies, 2009)
The model of life cycle of electronic apparatus, based on thermodynamics approach at description of degradation processes which limit burn-time apparatus, is offered